Impact of COVID-19 lockdown on activity patterns and weight status among youths in China: the COVID-19 Impact on Lifestyle Change Survey (COINLICS) - Jia, Peng; Zhang, Lei; Yu, Wanqi; Yu, Bin; Liu, Meijing; Zhang, Dong; Yang, Shujuan (International Journal of Obesity, 2021)
Lockdown measures including school closures due to COVID-19 may affect youths' activity patterns and obesity status. This will be for the first time examined in China in this study on the basis of a large national sample from the COVID-19 Impact on Lifestyle Change Survey (COINLICS). Through an online questionnaire, 10,082 participants from high schools, colleges, and graduate schools, aged 19.8 ± 2.3 years, voluntarily reported their lifestyles and weight status before (January 2020) and after lockdown (April-May 2020). The significance of these changes was assessed between sexes and across education levels. We found that the youths' average body mass index significantly increased from 21.8 to 22.1 kg/m , with the prevalences of overweight/obesity and obesity increasing from 21.4% to 24.6% and from 10.5% to 12.6%, respectively. Also, significant decreases were seen in the frequency of engaging in active transport, moderate-/vigorous-intensity housework, leisure-time moderate-/vigorous-intensity physical activity, and leisure-time walking, while significant increases were observed in the average sedentary time during workdays and weekends, the average sleeping time during workdays and weekends, and screen time. Our findings would serve as important evidence for shaping global strategies to counteract or reverse the lockdown effects on youths' obesity.